2017
DOI: 10.1016/j.jfda.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective effect of Paeonia emodi via inhibition of advanced glycation end products and oxidative stress in streptozotocin–nicotinamide induced diabetic nephropathy

Abstract: The present study aimed to evaluate the effect of alcohol (PA) and hydroalcohol (PHA) extract of Paeonia emodi Royale roots in treatment of streptozotocin-nicotinamide induced diabetic nephropathy. Diabetes mellitus was induced in male Wistar rats by streptozotocin (65 mg/kg intraperitoneally) 15 minutes after nicotinamide (230 mg/kg, intraperitoneally) administration and diabetic nephropathy was assessed by measuring serum glucose, renal parameters (urea, uric acid, creatinine, and blood urea nitrogen level) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 45 publications
(51 reference statements)
3
21
0
Order By: Relevance
“… 52 AGEs accumulation is the only mechanism that leads to structural aberrations in kidneys of DN animals. 11 , 50 , 53 Inhibition of the formation of AGEs is a potentially therapeutic avenue in DN. The present study demonstrates that DAE and DHE exhibits potential inhibitory effect against the formation of AGEs in vitro .…”
Section: Discussionmentioning
confidence: 99%
“… 52 AGEs accumulation is the only mechanism that leads to structural aberrations in kidneys of DN animals. 11 , 50 , 53 Inhibition of the formation of AGEs is a potentially therapeutic avenue in DN. The present study demonstrates that DAE and DHE exhibits potential inhibitory effect against the formation of AGEs in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…F. vulgaris as a medicinal plant rich in antiinflammatory and antioxidant compounds such as spathulenol, carvacrol, alpha-pinene and limonene, and it has strong antiinflammatory and antioxidant properties [20,53,54]. Previous studies have indicated that ethnomedicinal plants rich in antiinflammatory and antioxidant compounds decrease weight, volumes and lengths of kidney and its subcomponents in STZ-induced nephrotoxicity in mice [55,56].…”
Section: Nephroprotective Effect Of F Vulgarismentioning
confidence: 99%
“…Ginger contains gingerol, which can inhibit production of nitric oxide, IL-6, and TNF in glial cells. Peony [ 32 ], Guizhi [ 33 ], and ginger have anti-inflammatory effects and can reduce expression of PGE2, NF- κ B, and other mediators of the inflammatory response. The chemical constituents in Gui-Zhi-Tang [ 34 ] were studied by rapid resolution liquid chromatography quadrupole time-of-flight mass spectrometry combined with rapid resolution liquid chromatography-diode array detector-ion trap mass spectrometry, and a total number of 187 compounds were detected.…”
Section: Discussionmentioning
confidence: 99%